Two-layer additively manufactured crown: Proof of concept. (September 2021) - Revilla-León, Marta; Zandinejad, Amirali
Abstract: Objectives: To assess the feasibility of additively manufacturing a crown with a 2-layer design. Methods: A mandibular first molar tooth preparation titanium die for a full coverage restoration was obtained. The die was used to design a monolayer (ML group) and 2-layer (2L group) anatomically contoured crown. In the ML group, the specimen was manufactured with a hard polymer (Rigur RGD450; Stratasys). In the 2L group, the crown was splinted into 2 parts: the intaglio that represented 25% of the total crown volume that was manufactured with a resilient polymer (Vero; Stratasys) and the exterior that represented the remaining crown volume that was manufactured with a hard polymer (Rigur RGD450; Stratasys). Specimens were manufactured using a material jetting printer (Connex3 Object260; Stratasys). The marginal and internal discrepancies of ML and 2L specimens were visually assessed. Results: The ML and 2L specimens were manufactured using a material jetting printer that obtained a visually acceptable marginal and internal discrepancy. Conclusions: The 2-layer dental crown can be manufactured using a material jetting printer. Clinical significance: Material jetting technology has the capability to fabricate a 2-layer dental crown design which can be fabricated using materials with different properties.